Graphene and graphene-like materials in biomass conversion: paving the way to the future. Issue 48 (28th November 2017) - Das, Vijay Kumar; Shifrina, Zinaida B.; Bronstein, Lyudmila M.
Abstract : In this review we identify the key factors for the successful design of catalysts based on graphene derivatives for biomass conversion and suggest our perspective for the development of this field. Abstract : Materials based on graphene and its derivatives have a dual relationship with biomass: (i) they can be synthesized using biomass or its platform chemicals and (ii) they can be employed as efficient catalysts or supports for nanoparticulate catalysts for biomass conversion. In this review article we discuss methods of catalyst synthesis using top-down and bottom-up approaches as well as different synthetic pathways where all or some catalyst components are prefabricated or the whole catalyst is prepared in situ from small molecules. We identify key factors influencing the efficiency of the catalysts formed and suggest our perspective for the development of this field.